University education and cervical artery dissection - Kellert, Lars; Grau, Armin J.; Pezzini, Alessandro; Debette, Stéphanie; Leys, Didier; Caso, Valeria; Thijs, Vincent N.; Bersano, Anna; Touzé, Emmanuel; Tatlisumak, Turgut; Traenka, Christopher; Lyrer, Philippe A.; et al. (Journal of neurology, 2018)
Background and purposeWe investigated whether university education is more likely in cervical artery dissection (CeAD)-patients than in age- and sex-matched patients with ischemic stroke (IS) due to other causes (non-CeAD-IS-patients).MethodsPatients from the Cervical Artery Dissection and Ischemic Stroke Patients study with documented self-reported profession before onset of IS due to CeAD (n = 715) or non-CeAD causes (n = 631) were analyzed. In the reported profession, the absence or presence of university education was assessed. Professions could be rated as academic or non-academic in 518 CeAD and 456 non-CeAD patients. Clinical outcome at 3 months was defined as excellent if modified Rankin Scale was 0-1.ResultsUniversity education was more frequent in CeAD-patients (100 of 518, 19.3%) than in non-CeAD-IS-patients (61 of 456, 13.4%, p = 0.008). CeAD-patients with and without university education differed significantly with regard to smoking (39 vs. 57%, p = 0.001) and excellent outcome (80 vs. 66%, p = 0.004). In logistic regression analysis, university education was associated with excellent outcome in CeAD-patients (OR 2.44, 95% CI 1.37-5.38) independent of other outcome predictors such as age (OR 0.97, 95% CI 0.84-0.99), NIHSS (OR 0.80, 95% CI 0.76-0.84) and local signs (OR 2.77, 95% CI 1.37-5.57).ConclusionWe observed a higher rate of university education in patients with CeAD compared with non-CeAD patients in our study population. University education was associated with favorable outcome in CeAD-patients. The mechanism behind this association remains unclear.